Dual antiplatelet therapy prolongation in high-risk patients with prior myocardial infarction: insights from the post-PCI registry. Issue 8 (August 2020) - Ferlini, Marco; Rossini, Roberta; Musumeci, Giuseppe; Cornara, Stefano; Somaschini, Alberto; Grieco, Niccolò; Marino, Marcello; Calchera, Ivan; Cardile, Antonino; Colombo, Paola; Martinoni, Alessandro; Ielasi, Alfonso; et al.
Abstract : Background: Patients surviving a myocardial infarction (MI) are at a heightened risk for recurrent ischemic events that can be reduced with the long-term addition of a second antithrombotic drug to aspirin. However, data about real prescription of this therapy are lacking and sometimes controversial. Methods: We aimed to describe the incidence and the determinants of a dual antiplatelet therapy (DAPT) prolongation beyond 12 months in a cohort of consecutive patients undergoing percutaneous coronary intervention (PCI) with prior MI undergoing PCI and features of high ischemic risk intended as age more than 65 years, second MI, type 2 diabetes mellitus, multivessel coronary artery disease (MVCAD) and chronic kidney disease (CKD). We analysed patients enrolled in the prospective 'Post-PCI' registry that included patients treated with PCI for stable coronary artery disease (CAD) or acute coronary syndromes. At 12 months' follow-up, we collected data about DAPT prolongation in patients with prior MI and at least one of the previous features of high risk who did not experience ischemic and bleeding events during the follow-up. Results: Among 1113 patients included in the registry, 778 (72%) presented the inclusion criteria for the present study: 434 (66%) were more than 65 years old, 245 (37%) had a second MI, 189 (29%) diabetes mellitus, 480 (73%) MVCAD and 216 (33%) CKD. Despite a DAPT being prescribed for 1 year in 86% of the patients, it was prolonged for over 12 months in 105 (16%) of them. At multivariable analysis, only second MI and MVCAD were independent predictors of DAPT prolongation in a model including age more than 65 years, diabetes mellitus, CKD and PCI on left main/left anterior descending coronary artery. We found no significant difference in DAPT prolongation according to a DAPT-score value at least 2 or based on the physician who actually performed the follow-up (clinical cardiologist, interventional cardiologist or other). Conclusion: In patients with prior MI and features of high ischemic risk undergoing PCI, the rate of DAPT prolongation beyond 12 months was low; recurrent MI and MVCAD appeared as its main determinants.